Glutamatergic Neurotransmission Controls the Functional Lateralization of the mPFC in the Modulation of Anxiety Induced by Social Defeat Stress in Male Mice - Santos-Costa, Nathália [UNESP]; Baptista-de-Souza, Daniela [UNESP]; Canto-de-Souza, Lucas [UNESP]; Fresca da Costa, Vinícius [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Frontiers, 2021)
The rodent medial prefrontal cortex (mPFC) is anatomically divided into cingulate (Cg1), prelimbic (PrL), and infralimbic (IL) subareas. The left and right mPFC (L and RmPFC) process emotional responses induced by stress-related stimuli, and LmPFC and RmPFC inhibition elicit anxiogenesis and anxiolysis, respectively. Here we sought to investigate (i) the mPFC functional laterality on social avoidance/anxiogenic-like behaviors in male mice subjected to chronic social defeat stress (SDS), (ii) the effects of left prelimbic (PrL) inhibition (with local injection of CoCl2) on the RmPFC glutamatergic neuronal activation pattern (immunofluorescence assay), and (iii) the effects of the dorsal right mPFC (Cg1 + PrL) NMDA receptor blockade (with local injection of AP7) on the anxiety induced by left dorsal mPFC inhibition in mice exposed to the elevated plus maze (EPM). Results showed that chronic SDS induced anxiogenic-like behaviors followed by the rise of ΔFosB labeling and by ΔFosB + CaMKII double-labeling bilaterally in the Cg1 and IL subareas of the mPFC. Chronic SDS also increased ΔFosB and by ΔFosB + CaMKII labeling only on the right PrL. Also, the left PrL inhibition increased cFos + CaMKII labeling in the contralateral PrL and IL. Moreover, anxiogenesis induced by the left PrL inhibition was blocked by NMDA receptor antagonist AP7 injected into the right PrL. These findings suggest the lateralized control of the glutamatergic neurotransmission in the modulation of emotional-like responses in mice subjected to chronic SDS.
Keywords: anxiety; CaMKII; chronic social defeat stress; glutamatergic neurotransmission; mice; mPFC; ΔFosB